Diálogos com a história nas Novas cartas chilenas, de José Paulo Paes - Triques, Fernando Tadeu (2023)
The present work focused on the study of Novas cartas chilenas, by José Paulo Paes, written throughout 1954 and published by Revista Brasiliense, in 1956. It’s composed of twenty poems, the book allows, using satirical strategies – parody, debasement, ekphrasis, epigram, aphorism, etc. – the establishment of dialogues with some specific moments of Brazilian history. Certainly, with ideological inclination and aesthetic concern, José Paulo Paes used the Cartas chilenas, which were pertinent to the Inconfidência Mineira (1789) process and attributed to Tomás Antônio Gonzaga, for announcing to anonymous and absent audiences those new perspectives and interpretations about Brazil. Finally, the book marks a inflection point in the author’s poetic development as evidenced by the observation that the synthesis, the thematic and formal forcefulness, the ironic thrust, the epigram tendency and the aphorism, the clear ideological inclination and the undeniable creativity become recurrent in aesthetic traits of his later works.